Pertanggung jawaban Pidana Pengurus Yayasan Panti Asuhan Tunas Bangsa Terhadap Tindak Pidana Kekerasan Anak Menurut Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak Di Wilayah Hukum Kota Pekanbaru - Sintia Monika; Dessy Artina; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Some actions of the management of the foundation have even led to criminal actions. For example,letting the owner of an orphanage violate children in an orphanage, knowing the owner of an orphanagefoundation has committed a crime of violence but does not prevent it, is negligent in carrying outstewardship duties as it is so that the victim dies. So far, very little punishment has been carried out on themanagement of the foundation, even though the sentence is clearly condemned because the management ofthe foundation is one of the legal subjects. The absence of punishment against the foundation's managementwas the background of this research. In accordance with the description above, the authors are interested inconducting research under the title Criminal Liability Against Administrators of the Tunas BangsaOrphanage Foundation Against the Crime of Child Violence according to Law Number 35 of 2014concerning the Protection of Children in the Legal Territory of Pekanbaru City. This thesis aims to find outwhether or not administrators of the nation's orphanage foundations can be held accountable or not if thereis a criminal act in the nation's foster home foundation and to find out how the nation's foster careinstitutions are convicted so that the orphanage foundation administrators can be convicted.The type of research used in writing this law is empirical sociological legal research, namely themethod or method used in legal research conducted by examining existing library materials by looking atevents or facts that occur in the social environment. The nature of this research is descriptive. This studyuses primary data, namely data that the author gets / gets through respondents (field) that are in accordancewith the problem and secondary data, namely data that has been prepared.From the results of the problem research there are two things that can be concluded, firstly, themanagement of the foundation can be criminal if there is a crime that causes casualties because themanagement is an important organ in the foundation. Second, the punishment of the management of thefoundation can be carried out in accordance with the Foundation Law and the Child Protection Act.Keywords: Accountability, Foundation Management.